New evidence on the association of occupation with amyotrophic lateral sclerosis: A register-based case-control study in Finland - Saastamoinen, Peppiina; Laaksovirta, Hannu; Leino-Arjas, Päivi; Rahkonen, Ossi (Frontiers in Neurology, 2022)
Objectives Amyotrophic lateral sclerosis (ALS) is a serious neurodegenerative disease that usually leads to death within a few years from diagnosis. The risk factors for ALS are still largely unknown. However, it is assumed that environmental factors play a role in disease onset. Occupation is suggested as a potential risk factor, but findings are inconsistent. The aim of this study was to assess the association of occupation with ALS in Finland. Register data were used to avoid recall bias and to obtain a large enough sample to detect the potential associations. Methods This case-control study included ALS cases that occurred between 1980 and 2015 in Finland (n = 4,781). ALS cases were identified from the causes of death register. For each ALS case, six controls were selected matched for sex and birth-year. The date of death of the ALS case was set as index date. Information on occupation was obtained from Statistics Finland for all subjects. The focus was on the longest-held occupation on 2-digit level (70 groups). The association of occupation with ALS was analyzed using conditional logistic regression. Results Compared to “clerical work and other office work,” the risk of ALS was increased in “packing and wrapping work” (OR 1.53, 95% CI 1.08–2.17), “laundering, dry cleaning and pressing work” (OR 1.83, 95% CI 1.08–3.08), and “travel service work” (OR 8.75, CI 2.76–27.74). A decreased risk was found in “planning, administrative and research work in the technical fields” (OR 0.69, 95% CI 0.48–0.98). Of the significant associations identified, only “travel service work” was significant after FDR multiple testing correction. Conclusions This study identified occupations in which the risk of ALS was increased. Further studies are needed to pinpoint the potential exposures in these occupations that may trigger the disease.